2016
DOI: 10.1002/jor.23252
|View full text |Cite
|
Sign up to set email alerts
|

Osteophyte formation after ACL rupture in mice is associated with joint restabilization and loss of range of motion

Abstract: Osteophytes are a typical radiographic finding during osteoarthritis (OA). Osteophytes are thought to form in response to joint instability, however the time course of osteophyte formation and joint stabilization following joint injury is not well understood. In this study, we investigated the time course of osteophyte formation and joint function following non-invasive knee injury in mice. We hypothesized that initial joint instability following knee injury would initiate osteophyte formation, which would in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 22 publications
(29 reference statements)
3
34
2
Order By: Relevance
“…Increases in mechanical loading may thus promote osteophyte formation, and the current study demonstrated that osteophyte size increased as the alignment deteriorated. These results were supported by previous animal and clinical studies involving knees with a damaged or deficient anterior cruciate ligament, in which the loads to the knee joint were mainly increased in the AP direction.…”
Section: Discussionsupporting
confidence: 85%
“…Increases in mechanical loading may thus promote osteophyte formation, and the current study demonstrated that osteophyte size increased as the alignment deteriorated. These results were supported by previous animal and clinical studies involving knees with a damaged or deficient anterior cruciate ligament, in which the loads to the knee joint were mainly increased in the AP direction.…”
Section: Discussionsupporting
confidence: 85%
“…The formation of fracture calluses and osteophytes is generally similar, and recapitulate the differentiation pattern in the growth plate during development . Both begin as cartilaginous soft tissue that gradually ossifies to become bone, both are highly modulated by the TGF‐ÎČ superfamily, and both are thought to act as mechanical stabilizers . We previously showed that chondro/osteophyte formation after injury correlates with increasing joint stability after ACL rupture in mice, with a full return to control levels after 8 weeks .…”
mentioning
confidence: 71%
“…Whole knee joints and femora were scanned using ÎŒCT (SCANCO ÎŒCT 35, BrĂŒttisellen, Switzerland) to determine total mineralized osteophyte and fracture callus volumes at 14, 21, and 28 days post‐injury. Earlier time points were not evaluated using ÎŒCT because we previously found that mineralized osteophytes were not detectable by ÎŒCT until at least 2 weeks following non‐invasive knee injury . Scans were performed according to rodent bone structure analysis guidelines (X‐ray tube potential = 55 kVp, intensity = 114 ÎŒA, 10 ÎŒm isotropic nominal voxel size, integration time = 900 ms) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sections were stained with Safranin‐O–fast‐green to assess osteophyte formation and articular cartilage degeneration. The osteophyte (including chondrophyte) areas were quantified using freehand traces in ImageJ (National Institutes of Health, Bethesda, MD) . Histologic grading of articular cartilage damage severity was performed using the scoring system reported by Kamekura et al, which consisted of a 0‐4 scale for cartilage degeneration (0: No apparent changes; 1: Loss of superficial zone in articular cartilage; 2: Defects limited above tidemark; 3: Defects extending to calcified cartilage; 4: Exposure of subchondral bone) and a 0‐3 scale for osteophyte formation (0: None; 1: Formation of cartilage‐like tissues; 2: Increase in cartilaginous matrix; 3: Endochondral ossification).…”
Section: Methodsmentioning
confidence: 99%